2010
DOI: 10.1021/om100583p
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin-Based Supramolecular P,N Bidentate Ligands and their Platinum and Rhodium Complexes

Abstract: We report the elaboration of supramolecular P,N bidentate ligands starting from mono-N,N-dialkylamino-β-cyclodextrins (CD) and an appropriate phosphane, namely the sodium salt of the bis(3-sodiosulfonatophenyl)(4-tert-butylphenyl)phosphane (2). The inclusion complexes stemmed from inclusion of 2 in the cavity of mono-N,N-diethylamino-β-CD (3) or monopyrrolidino-β-CD (4) have been characterized by NMR and isothermal titration calorimetry (ITC) measurements. A 1/1 stoichiometry was established for each complex, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Analogues of the b-cyclodextrin derivative 61, bearing more basic amino groups, favour the formation of neutral Pt and Rh complexes featuring the supramolecular P,N ligand in a chelate coordination mode. 199 The related rhodium P, N-complexes are selective catalysts for the hydroformylation of styrene in water (b : l ratio = 10.1 in the best case). 200 Gennari and co-workers have used p-p interactions between electron-rich and electron-poor arenes as the driving force to generate chiral hetero-complexes containing a combination of two different monodentate phosphane ligands.…”
Section: Formation Of Bidentate Ligandsmentioning
confidence: 99%
“…Analogues of the b-cyclodextrin derivative 61, bearing more basic amino groups, favour the formation of neutral Pt and Rh complexes featuring the supramolecular P,N ligand in a chelate coordination mode. 199 The related rhodium P, N-complexes are selective catalysts for the hydroformylation of styrene in water (b : l ratio = 10.1 in the best case). 200 Gennari and co-workers have used p-p interactions between electron-rich and electron-poor arenes as the driving force to generate chiral hetero-complexes containing a combination of two different monodentate phosphane ligands.…”
Section: Formation Of Bidentate Ligandsmentioning
confidence: 99%
“…The art of synthesizing efficient molecular receptors and phosphines has been of tremendous help in the understanding of the catalytic process and now opens fascinating opportunities in the area of biphasic aqueous catalysis. For example, the formation of inclusion complexes between modified CDs and appropriate water soluble phosphines can be advantageously used to design new water soluble self-assembled supramolecular bidentates ligands for aqueous organometallic catalysis [95,96]. …”
Section: Discussionmentioning
confidence: 99%
“…14 Concurrently to the strategies developed in organic media, we demonstrated that the supramolecular approach was applicable to water-soluble bidentate ligands through hydrophobic effects using an appropriate cyclodextrin (CD)/phosphane combination. 15,16,17,18 More precisely, we showed that CDs functionalized on their primary face by nitrogen donor groups could partially include within their cavity a water-soluble sulfonated phosphane to form supramolecular PN ligands. The resulting self-assembled entities were capable of coordinating platinum and rhodium complexes in a κ 2 -P,N coordination mode, the CD simultaneously acting as a first-and secondsphere ligand (Scheme 1).…”
Section: Introductionmentioning
confidence: 92%